2009
DOI: 10.1097/cad.0b013e328330098d
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin enhances the anticancer effect of β-lapachone by upregulating NQO1

Abstract: NAD(P)H:quinone oxidoreductase (NQO1) has been reported to play an important role in cell death caused by beta-lapachone (beta-lap), 3,4-dihydro-22,2-dimethyl-2H-naphthol[1,22b]pyran-5,6-dione. This study investigated whether cisplatin (cis-diamminedichloroplatinum) sensitizes cancer cells to beta-lap by upregulating NQO1. The cytotoxicity of cisplatin and beta-lap alone or in combination against FSaII fibrosarcoma cells of C3H mice in vitro was determined with a clonogenic survival assay and assessment of gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
(94 reference statements)
0
36
0
Order By: Relevance
“…After incubation overnight at 37 C under 5% CO 2 atmosphere, the medium was replaced with fresh medium only or medium containing specific amounts of b-lap and the cells were incubated for varying lengths of time at 37 C. The cells were then rinsed twice with medium, and cultured with complete medium for 7-9 days at 37 C. The resultant colonies were fixed with a mixture of methanol and acetic acid (10 : 1 v/v), stained with 1% crystal violet, and the colonies containing more than 50 cells were counted. The role of NQO1 in the cell death caused by b-lap was studied by determining the influence of dicoumarol, an inhibitor of NQO1 [3,25,26,35,36], on the b-lap-induced clonogenic cell death.…”
Section: Cells and -Lapachonementioning
confidence: 99%
See 1 more Smart Citation
“…After incubation overnight at 37 C under 5% CO 2 atmosphere, the medium was replaced with fresh medium only or medium containing specific amounts of b-lap and the cells were incubated for varying lengths of time at 37 C. The cells were then rinsed twice with medium, and cultured with complete medium for 7-9 days at 37 C. The resultant colonies were fixed with a mixture of methanol and acetic acid (10 : 1 v/v), stained with 1% crystal violet, and the colonies containing more than 50 cells were counted. The role of NQO1 in the cell death caused by b-lap was studied by determining the influence of dicoumarol, an inhibitor of NQO1 [3,25,26,35,36], on the b-lap-induced clonogenic cell death.…”
Section: Cells and -Lapachonementioning
confidence: 99%
“…It was reported that b-lap causes DNA damage, thereby inducing H2AX foci formation [24], and we have recently demonstrated that b-lap-induced H2AX foci formation is markedly increased when the cells are pre-treated with ionising radiation [25] or cisplatin [26]. Takahash et al [27] observed that heat shock induced H2AX foci, and concluded that the heat-induced H2AX foci formation was due to DNA DSB.…”
mentioning
confidence: 97%
“…In addition, NQO1 has been shown to be an important factor in β-lapachone-induced cell death in many kinds of cancer cells (Pink et al, 2000;Reinicke et al, 2005), including breast cancer (Tagliarino et al, 2003), glioma (Park et al, 2011), and prostate cancer (Pink et al, 2000). In this context, other methods have been examined to increase NQO1 expression or activity in cancer cells (Terai et al, 2009;Tan et al, 2012;Satsu et al, 2012) in order to increase the clinical efficacy of β-lapachone. More recently, the genotoxic impact and genotoxic activities of the combination of β-lapachone and hydroxyurea (another anticancer drug and an inhibitor of ribonucleotide reductase) were reported in Allium cepa root meristem cells (Zabka et al, 2013).…”
Section: Mnpces (N)mentioning
confidence: 99%
“…However, it is also possible that β-lapachone induced a small number of DNA strand breaks owing to its ability to produce activated oxygen species (Docampo et al, 1979;Molina Portela and Stoppani, 1996;Molina Portela et al, 1996). β-lapachone (3,4-dihydro-2,2-dimethyl-2H-naphthol[1,2-b] pyran-5,6-dione, ARQ 501), a natural o-naphthoquinone and a major component in an ethanol extract of H. impetiginosus bark, displayed promising antitumor activity in various tumor cells (Pardee et al, 2002;Tagliarino et al, 2003;Terai et al, 2009;Tan et al, 2012) and has been tested as an antitumor drug in phase I, II, and III clinical trials in combination with other chemotherapeutic agents (Pardee et al, 2002;Bentle et al, 2007). The anticancer activity of β-lapachone may involve its catalysis by NAD(P) H:quinone oxidoreductase (NQO1, DT-diaphorase), which used NAD(P)H or NADH as an electron source to yield the two-electron reduction of β-lapachone (Pardee et al, 2002;Reinicke et al, 2005).…”
Section: Mnpces (N)mentioning
confidence: 99%
“…Importantly, the NQO1 content in various human cancer cells is significantly greater than that observed in normal tissues implying that tumors may be preferentially damaged by β-lap. Furthermore, NQO1 expression in cancer cells can be increased by a number of different types of stresses such as ionizing radiation (Choi et al, 2007), heat shock (Park et al, 2005b) and certain chemotherapeutic drugs such as cisplatin (Terai et al, 2009). These observations strongly indicated that conventional cancer treatments may increase the sensitivity of the cancer to β-lap treatment by increasing NQO1 activity in the target tumor cells (Park et al, 2005b;Suzuki et al, 2006;Choi et al, 2007;Song et al, 2008).…”
Section: Introductionmentioning
confidence: 99%